Transplant Tolerance, Not Only Clonal Deletion - Hall, Bruce M.; Verma, Nirupama D.; Tran, Giang T.; Hodgkinson, Suzanne J. (Frontiers in Immunology, 2022)
The quest to understand how transplanted tissue could not reject and survive in a disparate host, led to fundamental concepts in immunology. Clonal deletion theory was made to explain observations made in the 1940-60s. At that time basic mechanisms of immune response were not known, including the role of lymphocytes and T cells in rejection. Yet this theory has dominated the interpretation of immune function for over 60 years. Alloantigen exposure, in utero or as a neonatal, led to deletion of donor reactive cells using mechanism similar to the elimination of self-reactive cells. These finding are reassessed in the light that T regulatory cells are produced by neonatal thymus. In the 1960’s “operational tolerance”, then described as specific unresponsiveness, was shown to develop in adult rodents after short-term therapies that modified the rejection response. Over time, these animals developed alloantigen specific tolerance to the graft but retain the capacity to effect rejection of third-party grafts. These animals had a “split tolerance” as peripheral lymphocytes from these animals responded to donor alloantigens in graft versus host assays and in mixed lymphocyte cultures, indicating there is no clonal deletion. Investigation of this phenomenon excluded many mechanisms, including anti-donor antibody blocking rejection as well as anti-idiotypic antibodies and T cells. This split tolerance can be transferred to a second immune-depleted host by T cells. These tolerant T cells effect rejection of third-party grafts. Tolerance transferring T cells, lose their suppressing function in culture with donor antigen, but this function was preserved in the presence of cytokine rich supernatant. This led to the identification of the CD4+CD25+T regulatory cell. The heterogeneity of CD4+CD25+Foxp3+T cells and their role in transplant tolerance is reviewed.